STRATEGI MANAJEMEN RISIKO PEMBIAYAAN MURABAHAH PADA PEMBIAYAAN KREDIT PEMILIKAN RUMAH SYARIAH - Hafsah Umar, St (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2020)
This study aims to know and explained about risk management strategy of murabahah costing by Syariah Mandiri Bank in handling of costing syariah house ownership credit. These research was qualitative in decriptive approach. Data analysis start of the gathering data then data analysis suitable with reduction, preparation, verification and conclusion. The result of research to proof that the risk management in murabahah costing on Syariah Mandiri Bank represent the attempt of minimalization of risk financial, as well as in pra contract or pasca contract as well as the risk in costing, risk of market and risk of operational. The risk management strategy suitable with Standard Operational Procedure from internal banking, identification to selection of customer, analysis measure about financial condition of customer with 5C analysis, monitoring of risk mitigation after contract with controlling of system computer program sigma and handling of risk through risk management include user, system and time limit.